1984
DOI: 10.1021/i200026a026
|View full text |Cite
|
Sign up to set email alerts
|

Improving sieve tray performance with knitted mesh packing

Abstract: Wadsworth, M. E.; roves, R. D. Trans. Soc. Min. Eng. A I M Perry, R. H.; Chllton, C. H. "Chemlcai Englneers' Handbook", 5th ed.; Szekeiy, J.; Themeiis. N. J. Wiley: New York, 1971; Chapter 17. Vlzsolyi, E. et al.Sieve trays have become popular contacting devices for mass and heat transfer applications because of their relative simplicity and low cost. As a result, much has been published in recent years on their hydraulic and mass transfer performance. However, little has appeared on improving contact performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…This increase in Murphee efficiency can be explained by the fact that the addition of packing enhances the contat between liquid-vapor, as explained in Figure 4. Also, the froth with smaller bubble size tends to have a higher surface tension (Spagnolo, D. A., et al, 1984). (Chen, G. X., et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in Murphee efficiency can be explained by the fact that the addition of packing enhances the contat between liquid-vapor, as explained in Figure 4. Also, the froth with smaller bubble size tends to have a higher surface tension (Spagnolo, D. A., et al, 1984). (Chen, G. X., et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…But it is not suitable for low flow rates liquid. (Spagnolo, D. A., & Chuang, K. T., 1984) are the pioneer to reveal on the possibility of combining sieve tray column with packing. To be precise, they incorporated a knitted mesh packing with bed size of 25 mm on the trays for the production of Girdler-Sulfide heavy water at the operating pressure and temperature of 2.17 MPa and 32 °C, respectively, where they found increasing tray efficiency by 3-20%.…”
Section: Introductionmentioning
confidence: 99%
“…Unfor- (95-125 "C). Figure 4 shows a simplified schematic of the GS pilot plant which has been described elsewhere (Spagnolo and Chuang, 1984;Spagnolo and Chuang, 1986). A 311 mm diameter three tray column, consisting of trays having perforations of 12.7 mm diameter, an open hole area of 10.7% and tray spacing of 381 mm was used.…”
Section: Cpllmentioning
confidence: 99%
“…To monitor heat transfer tray performance utilizing the Results GAMMA SCANNING model previously discussed, three measurements were required; overall heat transfer tray efficiency ( E H V ) , tray froth height (hf) and average froth density ( E~) . EHV was calculated from temperature measurements using Equation profile on the tray (Spagnolo and Chuang, 1984). production plant observations.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…Bain and Van Winkle (1961) and Smith (1963) found that trays with small hole size provided good vapour-liquid distribution and reduced weeping, while increasing tray efficiency by producing small bubbles with large interfacial area. Spagnolo and Chuang (1984) were the first to report on the performance of sieve trays combined with knitted mesh packing for heavy-water production in an absorption column. However the expense of manufacturing trays with holes smaller than 2 mm and the difficulty in avoiding clogging of these holes limits their applications to a few very clean systems.…”
mentioning
confidence: 99%